TDP-43 nuclear retention is antagonized by hypo-phosphorylation of its C-terminus in the cytoplasm - Célia Rabhi; Nicolas Babault; Céline Martin; Bénédicte Desforges; Alexandre Maucuer; Vandana Joshi; Serhii Pankivskyi; Yitian Feng; Guillaume Bollot; Revital Rattenbach; David Pastré; Ahmed Bouhss (Communications Biology)
Abstract Protein aggregation is a hallmark of many neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS), in which TDP-43, a nuclear RNA-binding protein, forms cytoplasmic inclusions. Here, we have developed a robust and automated method to assess protein self-assembly in the cytoplasm using microtubules as nanoplatforms. Importantly, we have analyzed specifically the self-assembly of full-length TDP-43 and its mRNA binding that are regulated by the phosphorylation of its self-adhesive C-terminus, which is the recipient of many pathological mutations. We show that C-terminus phosphorylation prevents the recruitment of TDP-43 in mRNA-rich stress granules only under acute stress conditions because of a low affinity for mRNA but not under mild stress conditions. In addition, the self-assembly of the C-terminus is negatively regulated by phosphorylation in the cytoplasm which in turn promotes TDP-43 nuclear import. We anticipate that reducing TDP-43 C-terminus self-assembly in the cytoplasm may be an interesting strategy to reverse TDP-43 nuclear depletion in neurodegenerative diseases.